Implementation of New Public Management (NPM) on the Performance of Public Sector Organizations in Indonesia - Zahra, Fatimah; Haliah, Haliah; Kusumawati, Andi (PT FORMOSA CENDEKIA GLOBAL, 2024)
The presence of New Public Management is intended as a renewal in public sector governance by introducing a system that has been practiced in private sector business activities. NPM is a form of bureaucratic reform paradigm in Indonesia due to the demands of society in the reform era. This study is a literature study that describes the implementation of NPM on the performance of public sector organizations in Indonesia. Through the analysis of relevant literature, the results of the study indicate that NPM which is expected to improve the performance of public sector organizations in Indonesia cannot be implemented perfectly due to limitations and the emergence of various problems in the implementation of NPM in public sector organizations.